A Double‐Blind, Randomized, Sham‐Controlled Trial of the Effect of a Radiation‐Attenuating Drape on Radiation Exposure to Endoscopy Staff During ERCP. (May 2015) - Muniraj, Thiruvengadam; Aslanian, Harry R; Laine, Loren; Farrell, James; Ciarleglio, Maria M; Deng, Yanhong; Ho, Henry; Jamidar, Priya A
Abstract : OBJECTIVES: Endoscopic retrograde cholangiopancreatography (ERCP) is associated with radiation exposure to the endoscopist and staff that may be significant in high‐volume centers. We investigated whether a radiation‐attenuating drape over the fluoroscopy image intensifier reduces radiation exposure during ERCP. METHODS: We performed a prospective, randomized, double‐blind trial of 100 therapeutic ERCPs at a tertiary‐care university center. Procedures were randomly assigned to groups receiving lead‐free radiation‐attenuating drapes ( n =50) or identical sham drapes ( n =50). The drapes were suspended around the fluoroscopy image intensifier during ERCP. The primary end point was the effective dose of radiation measured at the endoscopist's eye and neck, and at the assisting nurse's neck. The cumulative annual radiation exposure was also estimated. RESULTS: Fluoroscopy time, absorbed radiation dose, and dose area product were similar in the study groups. Mean effective dose for sham vs. radiation‐attenuating drape was 0.21±0.27 vs. 0.02±0.02 mSv at the endoscopist's eye, 0.35±0.44 vs. 0.03±0.03 mSv at the endoscopist's neck, and 0.27±0.34 vs. 0.02±0.02 mSv at the nurse's neck ( P <0.0001 for all comparisons). The relative risk reduction in radiation was 90%, 91%, and 93% at the three sites. At a high‐volume center in which an endoscopist performs 500 therapeutic ERCPs per year, the estimated cumulative annual effective dose at the endoscopist's eye level is 126 mSv with conventional protection and 12 mSv with a radiation‐attenuating drape, with the recommended limit being 20 mSv. CONCLUSIONS: The addition of a radiation‐attenuating drape around the image intensifier during ERCP significantly decreases radiation exposure to endoscopists and staff by ∼90%.